Rapid single pot synthesis of hierarchical Bi2WO6 microspheres/RGO nanocomposite and its application in energy storage: A supercritical water approach - Shetty, Manjunath; Manickavasakam, Karnan; Sabbanahalli, Chethan; Bekal, Chandrakantha; Izan Izwan, Misnon; Subrahmanya P, Ashwath; Roy, Kunal; Shivaramu, Prasanna Doddakunche; Baloor, Satish Shenoy; Rangappa, Dinesh (Elsevier Ltd, 2023)
The application of novel three-dimensional (3D) architectures in energy storage has fascinated researchers for a long time. The fast-paced technological advancements require reliable rapid synthesis techniques for developing multi-metal oxide (MMO) nanostructures. For the first time, we disclose the supercritical water method's use to synthesize a single-phase hierarchical three-dimensional (3-D) Bi2WO6 microsphere/Reduced Graphene Oxide (BWS/RGO) nanocomposite (SCW). Through various nano-characterization technologies, it is possible to confirm the sample characteristics and determine the nanocomposites' morphological, physical, and thermal properties. Additionally, the constructed coin cells' electrochemical behavior analyses shed light on their well-known higher initial cycle capacity of about 700 mAh g−1, demonstrating BWS nanostructures' superior capacity for lithium-ion storage (Li-ion). In contrast, in supercapacitor studies, a half-cell configuration with a 6 M KOH electrolyte achieved its maximum specific capacity of 1158C g−1 at a current density of 3 A g−1. Similarly, Trasatti's analysis shows that the false nature of the BWS/RGO material results in 83 % over capacitive behavior of 17 %. When it comes to effectively developing a material process technique for multi-metal oxides and associated RGO nanocomposites, the reported quick single-pot SCW approach has shown encouraging results.